Prevention and Detection of Heart Disease with Smart Wearable Band - Nivedita Shimbre (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Stress, a significant aspect of modern life, contributes to various health issues majorly heart attack. It caused due to obesity, pre-diabetes, and stress. Overcoming challenges in stress detection and management is very crucial. IoT plays important role to overcome this challenges. We are developing a smart wearable stress detection band using sensors such as GSR (Galvanic Skin Response) and HRV (Heart Rate Variability), along with PSS for stress measurement. This software continuously monitors stress levels and offers suggestions like exercise, meditation, and yoga, diet, reading books, healthy diet and many more. But in extreme cases, the band facilitates medical consultations through a user-friendly interface, enabling early detection and quick treatment to enhance life expectancy. This project aim is not only identifies stress but also pre-detects stress induced heart attacks. In critical situation system can swiftly notify medical agencies and family members contributing to early diagnosis and treatment. Overall, this initiative represents a significant step toward enhancing human well-being, promoting a smoother life, and increasing life expectancy by saving lives.